2021
DOI: 10.3389/fpls.2021.748130
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Improves Linoleic Acid Accumulation Possibly by Promoting Expression of EgFAD2 and Other Fatty Acid Biosynthesis Genes in Oil Palm Mesocarp

Abstract: Abscisic acid plays an important role in fruit development. However, the effect of ABA on fatty acid biosynthesis in oil palm is still unknown. In this study, ABA treatments (CK, A1–A4) were applied to oil palm fruit at 16 WAP (weeks after pollination), and fatty acids in the mesocarp at 24 WAP were analyzed by GC-MS. Results showed that linoleic acid content under treatment A2 (20 μM ABA) was significantly higher (slightly increased by 8.33%) than the control. Therefore, mesocarp samples of A2, and the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Studies have shown that spraying exogenous ABA on C. oleifera leaves under shortages of water significantly promotes the activity of genes such as accA , accB , FAD6 , FAD7 , and FAD8 in the leaves (Yang et al, 2024). According to another study, the application of external ABA promoted the transcription of FAD2 within oil palm fruit, which resulted in the accumulation of linoleic acid (Shi et al, 2021). This suggests the involvement of ABA in FA synthesis, with SNRK and PP2C as key elements in ABA signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that spraying exogenous ABA on C. oleifera leaves under shortages of water significantly promotes the activity of genes such as accA , accB , FAD6 , FAD7 , and FAD8 in the leaves (Yang et al, 2024). According to another study, the application of external ABA promoted the transcription of FAD2 within oil palm fruit, which resulted in the accumulation of linoleic acid (Shi et al, 2021). This suggests the involvement of ABA in FA synthesis, with SNRK and PP2C as key elements in ABA signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The genes FatI and FatB are key regulators engaged in the synthesis and accretion of medium-chain fatty acids (C8 to C14) in coconut meat. Their role is crucial in this process ( Shi et al, 2021 ). The expression of CpuFatI and CvFatB1 genes led to the production of capric acid (10:0) in Camelina oil, whereas the expression of CpuFatB4 gene ensued the production of myristic acid (14:0) and increased levels of palmitic acid (16:0) ( Kim et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies supported our results ( Gu et al., 2020 ). As mentioned above, in needles of WS pine seedlings, ABA levels significantly increased ( Figure 4A ) and (±)-ABA was in positive relation to MAG (18:3) ( Figure S5B and WS_L.vs.WW_L_neg_corr in Table S6 ), suggesting that ABA accumulation might improve unsaturated lipid biosynthesis in WS pine needles and sustain membrane stability and flexibility under drought stress, because ABA improves biosynthesis of some fatty acids in plants ( Norlina et al., 2020 ; Shi et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%